Production and Characterization of Scaffold made of Hydroxyapatite and Pectin of Green Cincau Leaf (Premna Oblongifolia Merr) - Habibie, S; Tristiyanti, Y; Gustiono, D; Harahap, M E; Chalid, S Y; Effendi, D (Journal of Engineering and Scientific Research, 2019)
Scaffold is a 3-dimensional matrix created as a new bone cell growth medium madefrom natural polymers and bioceramics. The extracted pectin from green Cincau leaves(Premna oblongifolia Merr) and hydroxyapatite (HA) are used in the manufacture ofscaffolds. Pectin was extracted using citric acid with variation concentration of 0, 0.1,0.2 and 0.3% (w / v). The 3% (w / w) HA-pectin mixture, dried freeze using a freezedryer. The characterization of extracted pectin and HA-pectin scaffold was thenperformed. The results showed that pectin of green Cincau leaves had low methoxylcontent, which was 1.364 to 5.022%. The resulting scaffold has a pore size rangingfrom 8.25 to 115 µm while the scaffold resistance to the load, ie 0.03 to 0.15 MPa. Thescaffold porosity that has been made is 15.33 to 40.97% while the density is 0.69 to1.02 g/cm3Keywords: Green Cincau Leaf, Hydroxyapatite, Pectin, Scaffold